IMPLEMENTATION OF ONLINE LEARNING AT SD NEGERI GEDANGAN SIDOARJO REGENCY - Evira Karunita Meidyanti; Ertien Rining Nawangsari (DIA: Jurnal Administrasi Publik, 2021)
This research is motivated by the many complaints from the implementation of online learning at various levels of education caused by the Covid-19 pandemic. What is felt is that in the education sector, learning is carried out face-to-face into online learning. The purpose of this study was to determine how the implementation of online learning at SD Negeri Gedangan Sidoarjo Regency and what are the supporting and inhibiting factors for implementing online learning at SD Negeri Gedangan Sidoarjo Regency. This research used descriptive qualitative research methods by observing, interviewing, and documenting. The results of this study indicate that online learning delivery communication is considered good enough, resources in online learning still have several problems with facilities that are still not fulfilled. The disposition is good with the assurance of the implementation of online learning by being given an internet quota, but it is still not optimal and still has some obstacles. The bureaucratic structure has gone well with the formation of the team. There are supporting factors, namely providing internet quotas, high participation, and conducting bureaucratic arrangements. Meanwhile, the inhibiting factor is inadequate facilities.